Removal of azo and anthraquinone dye from textile wastewater using ozone-based advanced oxidation processes / \c Siti Nasuha binti Sabri - Siti Nasuha Sabri (School of Environmental Engineering, Universiti Malaysia Perlis, 2018)
The research is to investigate the effectiveness of O3 and O3/S2O82- treatment for synthetic dye wastewater consist of diazo RR120 and anthraquinone RB19. In specific, the objectives of the research are ; to evaluate the performances of O3 and O3/S2O82- treatment for colour and COD removal of azo and anthraquinone dye ; to investigate the effect of operational parameters of ozone-based AOPs treatment performance ; to determine the optimum operational parameters by using Response Surface Methodology (RSM) by Box Behken Design (BBD).